Mechanochemical synthesis of the lead-free double perovskite Cs2[AgIn]Br6 and its optical properties. (10th May 2019) - Breternitz, Joachim; Levcenko, Sergiu; Hempel, Hannes; Gurieva, Galina; Franz, Alexandra; Hoser, Andreas; Schorr, Susan
Abstract: Hitting hard on the binary halides yields in the formation of Cs2 [AgIn]Br6 . The lead-free double perovskite marks, although not usable itself, a further step forward in finding sustainable and durable perovskite materials for photovoltaic applications. Cs2 [AgIn]Br6 is one of the prominent examples of double perovskites materials that have been suggested to circumvent the use of lead compounds in perovskite solar cells. We herein report the successful synthesis of the material as bulk powder using a mechanochemical approach. It crystallises in an elpasolite-type structure, an ordered perovskite superstructure, with a cell parameter of a = 11.00 Å. However, the compound exhibits a relatively large optical bandgap of 2.36 eV and is unstable under illumination, which impedes its use as solar absorber material at this early stage. Still, substitution of lead and the potential of this synthesis method are promising as well as the fruitful combination of theoretical considerations with experimental materials discovery.